A new generation of cryogenic high-Q Fabry–Perot resonators for ultrastable lasers. (June 2017) - Zhadnov, N.O.; Masalov, A.V.; Sorokin, V.N.; Khabarova, K.Yu.; Kolachevsky, N.N.
Abstract: We have performed a comparative analysis of the characteristics of laser resonators fabricated from various materials. The greatest attention is paid to the problem of Brownian noise leading to fluctuations in the resonator length and limitation of the frequency stability of a laser actively stabilised by the transmission peak of a high- Q Fabry–Perot resonator. A possibility of designing new-generation ultrastable laser systems based on cryogenic crystalline resonators is shown.